2020
DOI: 10.1103/physrevapplied.13.024025
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Large Lattice Relaxations in Photovoltaic Devices

Abstract: Temporal variations of Cu(In,Ga)Se2 photovoltaic device properties during light exposure at various temperatures and voltage biases for times up to 100 h were analyzed using the kinetic theory of large lattice relaxations. Open-circuit voltage and p-type doping increased with charge injection and decreased with temperature at low injection conditions. Lattice relaxation can account for both trends and activation energies extracted from the data were approximately 0.9 and 1.2 eV for devices with lower and highe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…One exception is our recent work which indicated a metastable increase in doping and V OC with forward‐voltage bias heat–light stress and losses in doping and V OC with V = 0 stress. [ 47 ]…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…One exception is our recent work which indicated a metastable increase in doping and V OC with forward‐voltage bias heat–light stress and losses in doping and V OC with V = 0 stress. [ 47 ]…”
Section: Figurementioning
confidence: 99%
“…[ 13 ] Other mechanisms that have been used to explain metastability in CIGS solar cells include the following: a) lattice relaxation around the ( V Se – V Cu ) divacancy defect complex, which has also been associated with persistent photoconductivity (PPC) of bulk CIGS material; [ 36–40 ] b) fast diffusion of Cu as interstitial Cu i + ions leads to increase in V oc upon forward bias soaking of the CIGS devices; [ 41,42 ] c) formation of In Cu DX‐center defects [ 43,44 ] which has been reported to have metastable shallow and deep donor configurations; d) photodoping of CdS or ZnS buffers; and [ 45,46 ] e) large lattice relaxation in the bulk CIGS driven by charge injection, similar to the ( V Se – V Cu ) mechanism, but with much longer characteristic times. [ 47 ] Although these studies have explored the effect of light soaking on Na‐PDT, RbF‐PDT, and CsF‐PDT devices, the combined effect of junction bias and light soaking on the metastability in CIGS solar cells remains relatively unexplored. One exception is our recent work which indicated a metastable increase in doping and V OC with forward‐voltage bias heat–light stress and losses in doping and V OC with V = 0 stress.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…in which V m ¼ φ m /q, with φ m the work function of the silver contact considered equal to 4.5 eV in this work [21] ; χ CIGS and E g,CIGS are, respectively, the electronic affinity and bandgap of CIGS, equal to 4.36 and 1.18 eV [22] ; N A is the density of shallow acceptor dopants in the CIGS layer to be determined with CV measurements; n i is the intrinsic density of carriers in the CIGS layer and equal to 1.4 Â 10 10 cm À3 [22] ; kT/q is the thermal energy. In a real case, the charged defects induce a voltage shift of the CV curves.…”
Section: Analysis Techniquementioning
confidence: 99%
“…Furthermore, Nordone et al. suggested that the activation energies for lattice relaxiation are sensitive to alkaline metal concentration and heating temperature …”
mentioning
confidence: 99%